ISLAMIC PERSONALIZATION AS THE BASIS OF RIGHT CLAIM SUBMISSION IN RELIGIOUS COURT - Rahadi Wasi Bintoro; Masruhan Masruhan (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Law Amendment of Religious Court Year 2006 brought revolutionary change toward the competencies of the religious court. Law of Religious Court mentioned that Religious Court is only for Muslims. Furthermore, several questions appear such as are they only Muslims who are able to have any case in Religious Court, how is about people who are non-Muslim or how is about other law subjects in form of legal entity whether they can have any case or not. This paper discusses the subjects and the objects of right claim in religious court. Based on the analysis, the judiciary for law subjects who are Muslims or obey to Islamic laws in muamalah matters is done based on Islamic principles. That is what is called as Islamic personalization. This needs to be emphasized that Islamic personalization is an absolute competence in which if it is broken, it will cause right claim become NO (niet ontvankelijke verklaard).Keywords: Islamic personalization, right claim, religious court